The Cost of Email Use in the Workplace: Lower Productivity and Higher Stress - Czerwinski, Mary; Johns, Paul; Iqbal, Shamsi (ACM CHI 2016, 2016)
While email has been shown to be beneficial in the workplace, studies have reported that extensive email use can bring costs. In this study we investigate exactly how time spent on email might be related to perceived productivity and stress in the workplace. We conducted a mixed methods approach using computer logging, biosensors and daily surveys with 40 information workers in their in situ workplace environments for two workweeks. We found that the more time employees spent on email, the lower was their perceived productivity and the higher their level of stress. The relationship between email use and productivity was mediated by a difficulty in focusing. We also found an effect of users’ email-checking habits: people who primarily check email in response to email notifications reported lower productivity compared to those who self-interrupt to check email. We discuss the implications of our results for improving organizational email practices.